ELZA SOARES, AT VARIOUS TIMES, BEING MARIA DA VILA MATILDE - Teodoro Vieira, Thatianne; Pereira de Lima, Angelita (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2026)
This work analyzes the song Maria da Vila Matilde, by Douglas Germano, performed by Elza Soares, from a feminist perspective. The song denounces violence against women in the domestic environment, which is what singer Elza Soares also experienced, described at different times in her career. Under a feminist analysis of the biography of Elza Soares and the song Maria da Vila Matilde, it is possible to understand the nuances of the dominant sex-gender system in our society reflected through violence against women.